Life satisfaction of Lublin nurses - Klaudia Olga Jakubowska; Mariusz Wysokiński; Wiesław Fidecki; Ewelina Snopek (Kazimierz Wielki University, 2017)
Abstract Introduction. Life satisfaction is a concept closely related to a feeling of happiness, well-being and comfort. It is felt by every man individually and is related to general evaluation of life. The subject of interest in this study is the level of life satisfaction among nurses and male nurses working in Lublin. Aim of the study. The aim of the study was to determine the level of life satisfaction among Lublin nurses and male nurses. Methods and materials. The study involved 14 male nurses and 109 nurses. The diagnostic survey with the use of the SWLS questionnaire in the adaptation of Zygfryd Juczyński and the respondents' particulars developed by the author. Statistical calculations were performed with the use of Statistica 9.1 computer programme. Findings. The mean value of life satisfaction was 23.17. Statistical analysis did not show statistically significant relationships between the demographic data of the respondents and the experienced life satisfaction. Such dependence occurs only between life satisfaction and the specificity of the respondents' work (p = 0.03). Conclusions. No relationship was found between life satisfaction among nurses and male nurses and demographic data. Life satisfaction among the respondents is hugely affected by the specificity of work in some departments.